STRATEGI KOMUNIKASI PEMASARAN DIGITAL UMKM MAKANAN KALENG DI MITRA TANI FARM - Siska Permatasari; Testa Pradia Nirwana; Febri Palupi Muslikhah (JURNAL SAHID DA'WATII, 2025)
Digital marketing has become an important strategy in developing businesses in the digital era, especially for Micro, Small and Medium Enterprises (MSMEs). This research aims to explore the digital marketing strategies implemented by Mitra Tani Farm MSMEs, especially in utilizing digital media to increase sales and expand market reach. Using qualitative research methods, data was obtained through structured interviews with the Mitra Tani Farm marketing team. The research results show that Mitra Tani Farm utilizes various digital platforms such as social media (Instagram), marketplaces (Shopee, Tokopedia), and websites to market their products. Leading products such as canned lamb and beef food showed increased sales through digital channels, despite challenges in marketplace competition. Apart from that, collaboration with resellers and providing attractive promotions via social media have also proven effective in attracting consumer interest. These results show that digital marketing provides great opportunities for MSMEs to win competition and increase sales, although appropriate strategies are needed to overcome challenges in an increasingly competitive digital market.